Self-regulation in the early years - Robson, Sue; Zachariou, Antonia (Learning Matters, 2022)
"This book supports students of Early Childhood Studies, Early Years and related disciplines to understand self-regulation in the early years. It explores what self-regulation is and includes evidence from cognitive, developmental and behavioural psychology and neuroscience. It asks why self-regulation is so central for children and why it is so important for practitioners to support and develop it in young children. The book explores how self-regulation underpins much of children's development, including social, emotional and cognitive development. Key contexts for self-regulation, in particular aspects such as play and talk, are covered."